An Assessment of School-Community Relationship in the Public Secondary Schools of Khyber Pakhtunkhwa, Pakistan (Journal of Social Sciences Review, 2021)
Human relationships directly influence the success of educational goals. As a result, a constructive partnership with instructors, administrators, heads, and students is required to achieve academic goals. It has been observed that good relationships among teachers, students, heads, parents, and the community decide a school's performance. As a result, the study aimed to investigate human relationship issues and their effects on school success to change the situation in the future. The study's participants were all heads of (GHS) Schools in Pakistan's Khyber Pakhtunkhwa province. The researcher used convenience sampling techniques to pick 65 heads from all GHSS in Malakand Division for the sample. Since it was a mixed approach study, a Likert-style questionnaire was used to collect quantitative data. A semi-structured interview guide was used to collect qualitative data from the purposefully chosen ten school heads. SPSS was used to tabulate and interpret the data, which was done using percentages and the Chi-square test.The bulk of students, according to the study, do not collaborate with school administrators. The analysis also found that parents, communities, PTCs, and BOGs are not entirely cooperative. Higher authorities do not perform their duties to the complete satisfaction of secondary school principals. In contrast, political influence has uprooted and ruined the whole educational structure. As a result, the study suggested that prominent representatives of the group (Khan, Malak, Pesh Imams) be welcomed to schools regularly to encourage parents and community members to cooperate and share school concerns and concerns with them. The Ministry of Education should include daily training and workshops for principals, BOGs, and PTCs to develop their leadership skills and increase community awareness and interest in school management issues. They will establish a sense of ownership as a result, and they will play an important role in the growth of organizations.
Keywords: human relationship, impact, school performance, secondary schools